The Effect of Coffee Farming on the Socio-Economic Improvement of Farmers in Siempat Nempu District, Dairi Regency - Wahyunita Sitinjak (Apollo: Journal of Tourism and Business, 2026)
This study aims to: 1) Determine the profile of coffee farming in Siempat Nempu District, Dairi Regency. 2) Determine the effect of coffee farming yields on the socioeconomic improvement of farmers in Siempat Nempu District, Dairi Regency. The sampling method used was purposive sampling of 30 people. The data collection techniques used were observation, interviews, and questionnaires. The data analysis techniques used descriptive analysis and multiple regression tests. The results of the study show that (1). Coffee farming activities are carried out by farmers with an average age of 42 years. The average level of formal education is 8 years. The average farming experience was 9 years. The average area of coffee plantations was 11 hectares. The average number of family members per farmer was 4 people. The average planting distance was 2 m x 2 m. (2). The results of the study show that there is an increase in the social and economic status of farmers caused by an increase in farming yields. Based on the partial t-test results: X1, X3, and X4 have a significant effect on Y. X4 is the most dominant variable with a p-value of 0.005. X2 is not significant, although its value is close to significant with a p-value of 0.055. The coefficient of determination (R2) test result is 54%, which means that the factors of pesticides (X1), planting distance (X2), fertilizer (X3), and labor (X4) affect agricultural yields (Y). The remaining 46% is influenced by other variables outside the scope of this study. The simultaneous test results show that the F value is 7.331 with a significance value of 0.000. Since the significance value is less than 0.05, it can be concluded that: Simultaneously, variables (X1) Pesticides, (X2) Planting Distance, (X3) Fertilizer, and (X4) Labor have a significant effect on variable (Y) Farming Yield. These four factors jointly affect Farming Yield (Y), but partially only the factors Pesticides (X1), Fertilizer (X3), and Labor (X4) have a significant effect.